Some innovative word-formation processes in popular Internet texts in Russian and Arabic: Некоторые Инновационные словообразовательные процессы в популярных интернет-текстах в русском и арабском языках (Journal of the College of Languages (JCL), 2021)
The present article discusses innovative word-formation processes in Internet texts, the emergence of new derivative words, new affixes, word-formation models, and word-formation methods. Using several neologisms as an example, the article shows both the possibilities of Internet word-making process and the possibilities of studying a newly established work through Internet communication. The words selected for analysis can be attributed to the keywords of the current time. (In particular, the words included in the list of "Words of 2019") there are number of words formed by the suffix method, which is the traditional method of the Russian word formation. A negation of these words is usually made through suffixes, dissonances or consonances with another negative word. Therefore, These words are formed through the addition of the neutral suffixes -ism, -ist, the words rashism (ideology of "Great Russia", from the Russia - Rasha, Rashka) and rashist (one who adheres to the ideology of rashism) have a negative connotation due not only to the negative connotation produced words (a person who, speaking in Russian, calls Russia Rushey, of course, shows his negative attitude towards the country), but also to the fact that they are associated with the words fascism and fascist. The Internet is considered a worldwide tool of communication used extensively by students, housewives and professionals as well The Internet is a heterogeneous environment consisting of various hardware and software configurations that need to be configured to support the languages used. The development of Internet content and services is essential for expanding Internet usage. Some of these improvements include the ability to support multiple languages and provide tools for creating and using multilingual content. For example:1-Site Analytics And Seo2 - Smm And Smo3- Aso4 - Email Marketing5 - Ppc - Marketing6 - Content Marketing7 - Influence Marketing8 - Other Plug ins To Improve EfficiencyАннотация В статье рассматриваются инновационные словообразовательные процессы в интернет-текстах, появление новых производных слов, новых аффиксов, словообразовательных моделей и способов словообразования. На примере нескольких неологизмов в статье показаны как возможности интернет-словотворчества, так и возможности изучения функционирования новообразований в интернет-коммуникации. Выбранные для анализа слова можно отнести к ключевым словам текущего времени. Отрицательная оценка в таких словах может быть задана производящим словом, суффиксом, неблагозвучием или созвучием слова с другим отрицательно оцениваемым словом. Так, образованные с помощью нейтральных суффиксов -изм, -ист слова рашизм (идеология «великорусскости», от пренебрежительного названия России - Раша, Рашка) и рашист (тот, кто придерживается идеологии рашизма) имеют ярко выраженную отрицательную окраску не только за счет отрицательной окраски производящего слова (человек, который, говоря по-русски, называет Россию Рашей, конечно,показывает свое отношение к стране, но и за счет того, что они ассоциируются со словами фашизм и фашист. Интернет, являясь международным средством коммуникации, должен поддерживать разные языки мира. В мире наблюдается рост числа пользователей его инструментов и приложений интернета среди разных людей, включая профессионалов, домохозяек и студентов. Интернет представляет собой гетерогенную среду, состоящую из различных конфигураций аппаратного и программного обеспечения, которые необходимо настраивать для поддержки используемых языков. Развитие интернет-контента и сервисов имеет важное значение для расширения использования интернета. Часть этих улучшений. Например:1-Аналитика Сайтов И Seo2- Smm И Smo3- Aso4- Email Маркетнинг5- Ppc - Маркетнинг6- Контент - Маркетнинг7- Маркетнинг Вляния8- Другие Плагины Для Повышения Эффекитвности включает в себя возможность поддержки нескольких языков и предоставление инструментов для создания и использования многоязычного контента.